miRNA and miRNA target genes in copy number variations occurring in individuals with intellectual disability - Qiao, Ying (BioMed Central, 2013)
BACKGROUND: MicroRNAs (miRNAs) are a family of short, non-coding RNAs modulating expression of human protein coding genes (miRNA target genes). Their dysfunction is associated with many human diseases, including neurodevelopmental disorders. It has been recently shown that genomic copy number variations (CNVs) can cause aberrant expression of integral miRNAs and their target genes, and contribute to intellectual disability (ID). RESULTS: To better understand the CNV-miRNA relationship in ID, we investigated the prevalence and function of miRNAs and miRNA target genes in five groups of CNVs. Three groups of CNVs were from 213 probands with ID (24 de novo CNVs, 46 familial and 216 common CNVs), one group of CNVs was from a cohort of 32 cognitively normal subjects (67 CNVs) and one group of CNVs represented 40 ID related syndromic regions listed in DECIPHER (30 CNVs) which served as positive controls for CNVs causing or predisposing to ID. Our results show that 1). The number of miRNAs is significantly higher in de novo or DECIPHER CNVs than in familial or common CNV subgroups (P < 0.01). 2). miRNAs with brain related functions are more prevalent in de novo CNV groups compared to common CNV groups. 3). More miRNA target genes are found in de novo, familial and DECIPHER CNVs than in the common CNV subgroup (P < 0.05). 4). The MAPK signaling cascade is found to be enriched among the miRNA target genes from de novo and DECIPHER CNV subgroups. CONCLUSIONS: Our findings reveal an increase in miRNA and miRNA target gene content in de novo versus common CNVs in subjects with ID. Their expression profile and participation in pathways support a possible role of miRNA copy number change in cognition and/or CNV-mediated developmental delay. Systematic analysis of expression/function of miRNAs in addition to coding genes integral to CNVs could uncover new causes of ID.